Correction for Flexural Vibration Analysis in Nonlocal Timoshenko Beams with Initial Stress - Guven, Ugur (ASCE-AMER SOC CIVIL ENGINEERS, 2016)
In the present work, the flexural vibration of nonlocal Timoshenko beams under an initial stress is readdressed. The complete effect of the initial stress is taken into account in the basic formulation. The analytical solution presented herein is based on Eringen's nonlocal elasticity theory. A numerical application of the corrected solution is carried out for a simply supported single-walled carbon nanotube (SWCNT). The comparative results show that the difference between the present corrected and the earlier solutions is not negligible. (C) 2015 American Society of Civil Engineers.
Keywords: CARBON NANOTUBES; WAVE-PROPAGATION; Engineering